2021
DOI: 10.3390/nu13062119
|View full text |Cite
|
Sign up to set email alerts
|

Is High Cholesterol Deleterious? An Alternative Point of View. Comment on Burén et al. A Ketogenic Low-Carbohydrate High-Fat Diet Increases LDL Cholesterol in Healthy, Young, Normal-Weight Women: A Randomized Controlled Feeding Trial. Nutrients 2021, 13, 814

Abstract: In their study of the effect of an LCHF-diet on blood lipids, Burén et al. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…On the other hand, another publication responding to these results suggests that this is not a cause for concern. The author argues that although many studies show an association between LDL-C and cardiovascular diseases, this is not conclusive of a causal relationship [48]. Another randomized controlled trial, however, reported a beneficial effect of the ketogenic diet on the lipid profile, including a reduction in LDL fraction cholesterol.…”
Section: The Effect Of the Ketogenic Diet On The Blood Lipid Profilementioning
confidence: 98%
“…On the other hand, another publication responding to these results suggests that this is not a cause for concern. The author argues that although many studies show an association between LDL-C and cardiovascular diseases, this is not conclusive of a causal relationship [48]. Another randomized controlled trial, however, reported a beneficial effect of the ketogenic diet on the lipid profile, including a reduction in LDL fraction cholesterol.…”
Section: The Effect Of the Ketogenic Diet On The Blood Lipid Profilementioning
confidence: 98%
“…We thank Ravnskov [ 1 ] for his interest in our recent publication [ 2 ]. In our study, low-density lipoprotein cholesterol (LDL-C) and Apolipoprotein B-100 (ApoB) almost doubled in young, healthy women when they followed the ketogenic low-carbohydrate high-fat (LCHF) diet.…”
mentioning
confidence: 99%